Tylosin Inhibits Streptococcus suis Biofilm Formation by Interacting With the O-acetylserine (thiol)-lyase B CysM - Zhou, Yonghui; Yu, Fei; Chen, Mo; Zhang, Yuefeng; Qu, Qianwei; Wei, Yanru; Xie, Chunmei; Wu, Tong; Liu, Yanyan; Zhang, Zhiyun; Chen, Xueying; Dong, Chunliu; et al. (Frontiers in Veterinary Science, 2022)
Streptococcus suis (S. suis) can decrease its virulence or modify local conditions through biofilm formation, which promotes infection persistence in vivo. Biofilm formation is an important cause of chronic drug-resistant S. suis infection. The aim of this study was to evaluate whether tylosin effectively inhibits S. suis biofilm formation by interacting with O-acetylserine(thiol)-lyase B (CysM), a key enzymatic regulator of cysteine synthesis. Biofilm formation of the mutant (ΔcysM) strain was significantly lower compared to the wild-type ATCC 700794 strain. Tylosin inhibited cysM gene expression, decreased extracellular matrix contents, and reduced cysteine, homocysteine, and S-adenosylmethionine levels, indicating its potential value as an effective inhibitor of S. suis biofilm formation. Furthermore, using biolayer interferometry technology and fourier-transform infrared spectroscopy, we found that tylosin and CysM could be combined directly. Overall, these results provide evidence that tylosin inhibits S. suis biofilm formation by interacting with CysM.